ANALYSIS OF INVESTMENT AND PRODUCTION COSTS OF HOPS IN THE CAIUÁ SANDSTONE REGION - Camargo, Ricardo Botelho; Silva, Gabriela Catuzo Canonico; Severino, José Júnior; Rickli, Max Emerson; Sakane, Kenny Tsuyoshi; Lopes, Ana Daniela; Francisco, João Paulo; Gazim, Zilda Cristiane (Revista de Ciências Empresariais da UNIPAR, 2024)
Hops (Humulus lupulus L.) is an ancient crop widely distributed across much of the world. The use of hops is very diverse. They are utilized in the pharmaceutical industry, in popular uses such as teas, and notably in the brewing industry, which is one of the main interests in hop cultivation since they are a key ingredient in beer formulation. Brazil is a significant consumer of hops; however, a large portion of its consumption comes from imported products. The country has great production potential, but its current production is still modest. Thus, the main objective of this study was to evaluate the initial investment and maintenance costs for hop cultivation in the Caiuá Sandstone region in northwestern Paraná State. To achieve this, an experiment covering 1,100 m² was conducted in the city of Umuarama, PR, assessing initial investment and production costs over two years. A significant portion of the investment was allocated to seedlings and trellis structures, while the most evident cost was the need for labor to maintain the crop. It was concluded that hop cultivation can be implemented; however, the initial investment is high, and there is a need to mechanize part of the management to mitigate labor costs.